BAGAN PENGERINGAN DEHUMIDIFIKASI BEBERAPA JENIS KAYU INDONESIA - Syarif Hidayat (Pusat Penelitian dan Pengembangan Hasil Hutan, 1991)
Since it• commercial introduction in the late 1960 deh midification haa become a very popular method of dryift6. npeciany for the •mailer operation drying hardwoods. Dehumidification haa also beenpractiaed in tome lndonaian mw- milla. However, the Information concerning the drying achedule of lndoneaian woods were .till limited. Thia report'Yi dacribe the dehumidification drying achedule for tome lndonaian commercial woods, •which were taken from Riau, Lampu